2022
DOI: 10.1186/s12968-022-00884-y
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal changes in ventricular size and function are associated with death and transplantation late after the Fontan operation

Abstract: Background Cross-sectional studies have reported that ventricular dilation and dysfunction are associated with adverse clinical outcome in Fontan patients; however, longitudinal changes and their relationship with outcome are not known. Methods This was a single-center retrospective analysis of Fontan patients with at least 2 cardiovascular magnetic resonance (CMR) scans without intervening interventions. Serial measures of end-diastolic volume ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…As the population of HLHS patients is growing and aging, there is increasing concern about the performance of the systemic RV. Previous imaging studies, including research from this group, have shown that ventricular function in HLHS patients declines over the years [5] , [14] although changes in functional parameters in pediatric and adolescent patients are relatively small [5] , [6] . Others have shown that CMR-derived variables seem to be predictive of long-term outcomes in Fontan patients [14] , [15] , [16] , [17] .…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…As the population of HLHS patients is growing and aging, there is increasing concern about the performance of the systemic RV. Previous imaging studies, including research from this group, have shown that ventricular function in HLHS patients declines over the years [5] , [14] although changes in functional parameters in pediatric and adolescent patients are relatively small [5] , [6] . Others have shown that CMR-derived variables seem to be predictive of long-term outcomes in Fontan patients [14] , [15] , [16] , [17] .…”
Section: Discussionmentioning
confidence: 88%
“…Previous imaging studies, including research from this group, have shown that ventricular function in HLHS patients declines over the years [5] , [14] although changes in functional parameters in pediatric and adolescent patients are relatively small [5] , [6] . Others have shown that CMR-derived variables seem to be predictive of long-term outcomes in Fontan patients [14] , [15] , [16] , [17] . It was shown that increased indexed end-diastolic volumes (EDVi) and rapid increase in EDVi predict adverse outcomes [14] , [16] , [17] .…”
Section: Discussionmentioning
confidence: 88%
“…This study reaffirmed that impaired ventricular ejection fraction, ventricular dilation, and RV or mixed ventricular morphology are established risk factors for poor clinical outcomes in patients with a Fontan circulation. 3,43,44 Multivariable analysis revealed that the association of adverse outcomes with markers of dyssynchrony is not independent of established conventional markers such as ventricular systolic dysfunction and dilation. Our findings of lower event-free survival in RV or mixed ventricular subtypes agree with prior large multicenter observational studies on Fontan patients, which have demonstrated lower long-term survival.…”
Section: Discussionmentioning
confidence: 99%
“…The preteen period may be too early to detect systolic dysfunction by CMR. Ghelani et al 18 recently described longitudinal changes in ventricular function and showed that on consecutive CMR, ejection fraction decreased over time among patients undergoing the Fontan procedure who were followed into early adulthood. Moreover, despite many risk factors considered and comprehensive prospective collection of data, even extensive modeling provided little insight into risk factors for lower RVEF.…”
Section: Discussionmentioning
confidence: 99%
“…Right ventricular function was measured with CMR as well as with 2-dimensional transthoracic echocardiography. Participants who underwent CMR were 10.9 years of age (interquartile range, 10.4-11.5) at the time of CMR, and, compared with those who did not have CMR, they had a significantly shorter hospital length of stay after the Norwood procedure (22 [interquartile range, [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] versus 28 days [interquartile range, 20-39]; P=0.02) and were more likely to be male (66% versus 47%; P=0.01; Table S2). Among the 177 participants who underwent CMR, RVEF was measurable in 168 (95%); the mean±SD for the overall cohort was 51.5±8.6% (RVPAS 51±9.…”
Section: Right Ventricular Functionmentioning
confidence: 99%